Can liver venous system diameters predict difficulty of laparoscopic liver resection? - Wojciech A. Serednicki; Anna Grochowska; Wacław Hołówko; Anna Dąbrowska; Natalia Janik; Michał Pędziwiatr (BMC Surgery)
Abstract Background Laparoscopic liver resection is a feasible and fast-disseminating, yet demanding technique that requires careful preoperative preparation. Due to its varying difficulty, many scales were developed to evaluate possible intraoperative difficulties and to select cases properly, especially during the learning curve. Our aim was to seek additional radiological parameters, such as liver venous system diameters, that may be useful in assessing possible intraoperative difficulties and predicting postoperative outcomes. Methods A retrospective study included 85 patients who underwent laparoscopic liver resection with previous computed tomography or magnetic resonance. Patients were divided into 3 groups of varying difficulty according to the Institute Mutualiste Montsouris (IMM) scale. Using syngo.via radiological system, the diameters of portal vessels and inferior vena cava were measured. Statistical analysis was performed to assess the correlation between measured radiological parameters and perioperative outcomes. Results Statistical analysis showed no correlation between portal and splenic vein diameter and perioperative outcomes in all patient population and in each of the IMM groups. Superior mesenteric vein (SMV) diameter correlated positively with intraoperative complication rate, but only in the IMM 2 group. Intraoperative Oslo complication rate was higher in < 10 mm splenic vein diameter group and the Clavien-Dindo complication rate was higher in < 13 mm SMV population, but only in the IMM 2 group. Conclusions Our study presents that portal system veins and inferior vena cava (IVC) diameter have low relevance to perioperative outcomes and don’t seem to be a good predictor of intraoperative blood loss and complication rate. However, they may be useful in selected difficulty groups, therefore further studies addressing this issue may be beneficial.